Sur une strategie adaptative pour les calc~ls non lineaires. Application aux calculs en viscoplasticite - Pelle, Jean Pierre; Ryckelynck, David (European Journal of Computational Mechanics, 1998)
We present an adaptive strategy for non-linear computations based on a non incremental method and on constitutive error estimCJtors which allow to control the quality of computations and to pilot the parameters of the algorithm. Some examples in th e case of viscoplastic structures are presented.